2001
DOI: 10.1136/jnnp.71.4.436
|View full text |Cite
|
Sign up to set email alerts
|

Suicide after traumatic brain injury: a population study

Abstract: Objectives-To determine the rates of suicide among patients who have had a traumatic brain injury. Methods-From a Danish population register of admissions to hospital covering the years 1979-93 patients were selected who had had either a concussion (n=126 114), a cranial fracture (n=7560), or a cerebral contusion or traumatic intracranial haemorrhage (n=11 766). All cases of deaths by the end of the study period were identified. Results-In the three diagnostic groups there had been 750 (0.59%), 46 (0.61%), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
226
4
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(248 citation statements)
references
References 18 publications
13
226
4
5
Order By: Relevance
“…36 Eighteen percent of our study population suffered head injury as well as ASCI. Several studies have demonstrated increased suicide risk following head injury, [37][38][39] which is independent of pre-injury mental state. 40 Although previous reports have highlighted the importance of intervention against suicide in the ASCI population as a whole, 34,41,42 it appears from our study that there is a real and particular need for such action in the group of people with ASCI suffered after suicide attempt.…”
Section: Discussionmentioning
confidence: 99%
“…36 Eighteen percent of our study population suffered head injury as well as ASCI. Several studies have demonstrated increased suicide risk following head injury, [37][38][39] which is independent of pre-injury mental state. 40 Although previous reports have highlighted the importance of intervention against suicide in the ASCI population as a whole, 34,41,42 it appears from our study that there is a real and particular need for such action in the group of people with ASCI suffered after suicide attempt.…”
Section: Discussionmentioning
confidence: 99%
“…26 There is now evidence that these effects are noticeable throughout adult life 26 and that a head injury may be associated with an increased risk of developing Alzheimer's disease and other dementias. 27,28 Table 2 summarises two studies 22,25 on the outcome of head injuries. It is worth highlighting that, of the individuals with an initial diagnosis of 'mild head injury':…”
Section: Do Helmets Really Work?mentioning
confidence: 99%
“…These effects appear to be time sensitive ie the time of injury influences the type of academic skill deficit and may influence its severity. 25 …”
Section: Do Helmets Really Work?mentioning
confidence: 99%
See 1 more Smart Citation
“…After TBI, the standardised mortality rate for suicide is increased threefold so that about 1% will commit suicide over a 15-year follow-up, the risk remaining fairly constant over this period 4 .…”
Section: Mood Disordersmentioning
confidence: 99%